Technology Entrepreneurship Project (ENT 600) : Asics / Nur Nabilah Awang Hanapiah - Awang Hanapiah, Nur Nabilah (2021)
First of all, the general information regarding the company has been collected. Primary and secondary source is used to gather the related information. The objective of the project is to figure on the background, organizational structure, products and services that Decathlon provides. In this case study, I have analyzed the strength, weaknesses, opportunities, and threats of this company by using SWOT analysis. This assignment is about the review aspects one of the sports products which is water bottle. So, the company that we choose is Asics which is it is one of the famous sports companies around the world. So, I studied regarding the product manufactured by Asics which is primarily a standard technology utilized by the company itself. Here, I will be explaining the problems of the water bottles that have catch my attention. The problem of the water bottles that I discovered is the water bottle does not have bottle cap that gives uncomfortable for the consumers to drink. Next, is the water bottle gives difficulties to carry. Lastly, it causes neck pain to the consumers while drinking. So, in this study, I will be explaining deeper regarding the problems and I would also be discussing the best alternatives solutions towards the problems.